Array CGH as a first-tier test for neonates with congenital heart disease. (6th November 2013) - Bachman, Kristine K.; DeWard, Stephanie J.; Chrysostomou, Constantinos; Munoz, Ricardo; Madan-Khetarpal, Suneeta
Abstract Objective Efficient diagnosis of an underlying genetic aetiology in a patient with congenital heart disease is essential to optimising clinical care. Copy number variants are one aetiology of congenital heart disease; the majority are identifiable by targeted fluorescence in situ hybridisation or array comparative genomic hybridisation, not by classical cytogenetic analysis. This study assessed the utility of array comparative genomic hybridisation as a first-tier diagnostic test for neonates with congenital heart disease. Study design A prospective chart review of neonates with congenital heart disease in the Cardiac Intensive Care Unit at Children's Hospital of Pittsburgh of UPMC was performed. Patients were tested by array comparative genomic hybridisation and classical cytogenetic analysis simultaneously. Data collected included all chromosome abnormalities detected, physical examination findings, and imaging results. McNemar's test was used to compare detection of array comparative genomic hybridisation and classical cytogenetic analysis. Results Of 45 patients, three (6.7%) had an abnormality detected by classical cytogenetic analysis and an additional 10 (22.2%) had a copy number variant detected by array comparative genomic hybridisation, highlighting an increased detection rate (p=0.008). Several of these copy number variants had unclear clinical significance, requiring additional investigation. The prevalence of dysmorphology and/or comorbidity in this population was 72%. Identification of dysmorphic features was greater when assessed by a geneticist than by providers of different subspecialties. Conclusions Array comparative genomic hybridisation has significant clinical utility as a first-tier test in this population, but it carries the potential for incidental findings and results of uncertain clinical significance. Collaboration between cardiologists and medical geneticists is essential to providing optimal clinical care.